2017
DOI: 10.1177/0020852317701824
|View full text |Cite
|
Sign up to set email alerts
|

Organizational goal ambiguity and senior public managers’ engagement: does organizational social capital make a difference?

Abstract: The Job Demands-Resources model highlights that aspects of the work environment that place high demands on employees are potential job stressors, which can reduce their levels of engagement with their work and organization. By contrast, social support for employees is a resource that can sustain their engagement and enable them to cope with high demands. We analyse the separate and combined effects of two key job demands and resources on the engagement of more than 4,000 senior public managers in ten European … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 60 publications
0
32
0
Order By: Relevance
“…The one-factor CFA model has a relatively very poor fit to the data (χ 2 = 7,059.89, df = 527, TLI = .560, NFI = .593, CFI = .610, RMSEA = .135), which suggests that there is little probability of common method bias. Second, we performed the more stringent unmeasured latent method factor technique (Andrews & Mostafa, 2019; Cole, Bedeian, & Bruch, 2011), which adds a latent common methods factor to the measurement model. This model showed a good fit to the observed data (χ 2 = 1,675.04, df = 478, TLI = .911, NFI = .904, CFI = .929, RMSEA = .061).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…The one-factor CFA model has a relatively very poor fit to the data (χ 2 = 7,059.89, df = 527, TLI = .560, NFI = .593, CFI = .610, RMSEA = .135), which suggests that there is little probability of common method bias. Second, we performed the more stringent unmeasured latent method factor technique (Andrews & Mostafa, 2019; Cole, Bedeian, & Bruch, 2011), which adds a latent common methods factor to the measurement model. This model showed a good fit to the observed data (χ 2 = 1,675.04, df = 478, TLI = .911, NFI = .904, CFI = .929, RMSEA = .061).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…The three dimensions of OSC are strongly interrelated and mutually reinforce each other. When people share the same values about their work, they will also be more likely to enjoy high-quality relationships with each other and regularly share information (Leana and Pil, 2006;Andrews and Mostafa, 2017).…”
Section: Self-sacrificial Leadership-employee Behaviours: Osc As a Mementioning
confidence: 99%
“…Although prior research has shown that OSC is beneficial to organizations (e.g. Leana and Pil, 2006;Andrews, 2010;Andrews and Mostafa, 2017), not much is known about how organizations could develop social capital (Pastoriza, Arino and Ricart, 2008;Parzefall and Kuppelwieser, 2012;Chuang, Chen and Chuang, 2013;Pastoriza and Arino, 2013). As stated by Pastoriza and Arino (2013; 1), "research has paid little attention to finding empirical evidence concerning how organizations may build social capital".…”
Section: Introductionmentioning
confidence: 99%
“…In spite of its importance to all types of organizations, very limited attention has been given by public administration scholars to the organizational antecedents of work engagement in public service organizations. Disengaged employees are costly to public organizations and could negatively influence public service delivery (Andrews & Mostafa, 2017). Therefore, identifying the drivers of work engagement in the public sector is important.…”
Section: Introductionmentioning
confidence: 99%